Integrated strategic segmentation as the element for forming the strategy of a trading enterprise - Нurzhii Nataliia (Management and Entrepreneurship: Trends of Development, 2017)
Purpose. The paper purpose is to define the strategic economic zones for large trading enterprises and to considerate the conceptual approach to the sequence of work in the segmentation of activities. Design/methodology/approach. The basic principles of the research are systematic and comparative methods, a structural-logical approach is used. Findings. The relevance of the topic is determined by the urgent need to increase the level of competitiveness of trade enterprises in a changing marketing environment. The subject of the research is the theoretical, methodological and practical aspects of strategic segmentation by trade enterprises in the course of their economic activities. The survey found that the marketing segmentation may serve as a basis for strategic analysis, but only on condition that the market situation is characterized by a stable excess of demand over supply. Furthermore, a general finding was that when comparing the problems and challenges both of longitudinal and transverse segmentation analysis the most significant is longitudinal one. Commercial enterprise strategy in turn is more linked to the achievement of the desired competitive position in a particular area of activity. Research limitations/implications. The scientific significance of the work lies in the author’s proposal to consider the symbiosis of macrosegmentation and microsegmentation of the market in the form of integrated strategic segmentation of trade enterprises. Product types, customer type, marketing technology, geographic region have been proposed as its criteria. Originality/value. The paper provides the results of the integrated strategic segmentation of a group of large enterprises of the “Brick-and-mortar” format, which marketing household appliances. Such information provides opportunities to identify the appropriate strategic economic zones and to determine the content of analytical work in segmenting their activities. That, as a consequents will create real opportunities for the proper determination and management of strategic change